2018
DOI: 10.1519/jsc.0000000000002214
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Changes in Jump Performance and Maximum Strength in a Cohort of National Collegiate Athletic Association Division I Women's Volleyball Athletes

Abstract: Kavanaugh, AA, Mizuguchi, S, Sands, WA, Ramsey, MW, and Stone, MH. Long-term changes in jump performance and maximum strength in a cohort of NCAA division I women's volleyball Athletes. J Strength Cond Res 32(1): 66-75, 2018-The purpose of this investigation was to quantify the magnitude of change in maximal strength and jumping abilities over approximately 1, 2, and 3 years of supervised sport and resistance training in National Collegiate Athletic Association (NCAA) division I women's volleyball athletes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…In addition, the transfer of weightlifting style training, has recently been reported to result in only small changes in jump performance over relatively short training periods (26), as observed here. In contrast however, traditional resistance training combined with weightlifting derivatives has been shown to enhance longitudinal maximal strength and jump performance (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the transfer of weightlifting style training, has recently been reported to result in only small changes in jump performance over relatively short training periods (26), as observed here. In contrast however, traditional resistance training combined with weightlifting derivatives has been shown to enhance longitudinal maximal strength and jump performance (30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no significant (p > 0.05) differences were observed between these lifts irrespective of the inclusion or exclusion of the catch phase (5,6). In addition, Suchomel et al (47) reported that the jump shrug, (similar to the mid-thigh pull but initiated with a countermovement and the athlete actually leaves the ground) resulted in significantly (p < 0.05) greater PF, peak velocity, and peak power compared to the hang power clean and hang high pull across all loads (30,45,65, 80% one repetition maximum [1RM] hang clean), indicating that the removal of a catch phase during a PC derivative is not detrimental to the peak power achieved. Similarly, additional studies by Suchomel et al (45,46) also reported greater relative PF, power, impulse, work, and peak RFD in the jump shrug compared to the hang power clean and hang high pull across loads (30,45,65, 80% 1RM hang clean).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The research hypothesis was that increased core stability indices would be associated with high scores of WAnT and Bosco test indices, and low BF. Since anaerobic capacity and body composition were related to performance [4,5], a potential association of core stability indices with these variables would highlight the relevance of core stability with performance.…”
Section: Introductionmentioning
confidence: 99%
“…A potential misbalance between torso flexors and extensors might be attributed to bidirectional variations (either high or low scores) of flexors muscle endurance rather than decreased extensors muscle endurance.Symmetry 2020, 12, 249 2 of 10 and tactical characteristics [2,3]. With regards to physiological characteristics, most studies have focused on jumping ability and anaerobic power so far showing that female volleyball players jumped high and were characterized by high levels of anaerobic power [4,5]. Both jumping ability and anaerobic power might vary by age with adults scoring higher than adolescents [6].…”
mentioning
confidence: 99%